The influence of users’ addictive behaviours on the relationships between information security countermeasures and risky cybersecurity practices - ALRASHDI, ALI SAEED (2020)
The emergence of the modern internet in 1990 and the development of web 1 was the first step on information sharing and reading-data, while the web 2 took a step closer and allowed peer-to-peer interactions with always an inter media system acting as a transmitter. Nowadays, web 3 is underway which will boost worldwide connectivity even further. The world is living the era of huge data flows, global scale interactions and social engagement of multicultural people in a worldwide network. People from various backgrounds and cultural dimensions are influencing the way that data are interpreted and managed through the technology driven system. Therefore, cyber security became extremely important and critical for organisations continuous operations. As the literature indicates the 95% of cyber security breaches are cause by a human error. Consequently, organisations worldwide are looking ways of minimising cyber threats that caused by human behaviour to improve information security. Currently, there is a lack of research on the role as well as the impact of the multi-behaviour countermeasures dimensions on information security. The main purpose of this research is to suggest a human behaviour information security countermeasures model for supporting investigation of and reasons for the main features of people’s risky behaviours in the context of information security within public organisations in the UAE. The research methodology used descriptive quantitative with linear regression analysis. The research used a questionnaire that was analysed with the software (SPSS) 24.0. Findings indicate that Attitude and self-efficacy have a direct influence on the attitudes towards cybersecurity countermeasures and Administrative, Managerial and Support countermeasures have a direct influence on the Security awareness countermeasures. The users’ addictive behaviours can influence both information security countermeasures and risky cybersecurity behaviour practices of the workforces of public organisations. Further research on employee behaviour can be studied over a longer period of time using a longitudinal study.